2013
DOI: 10.1136/emermed-2012-201904
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of resident and mid-level provider productivity in a high-acuity emergency department setting

Abstract: In a high-acuity area of the ED, MLPs see more patients per hour than residents, but generate fewer RVUs per patient. This suggests that residents may document more thoroughly than MLPs. Alternatively, MLPs may elect to see less sick patients even when working in a high-acuity area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Three small US studies of PAs in hospital settings published in 2013 and 2014 provided new positive evidence as to the contribution that PAs made to patient outcomes and resource use in a trauma-orthopaedic setting 32 and in low-and high-acuity emergency department (ED) settings. 33,34 One study 35 had reported that the indirect impact of employing PAs in a general surgical residency programme was to reduce the resident doctor workload, increase the doctors' ability to attend their training activities and improve results in their American Board of Surgery in Training Examination. In 2014, a study protocol was published for research investigating the substitution of medical doctors with PAs in hospitals in the Netherlands.…”
Section: Physician Associatesmentioning
confidence: 99%
“…Three small US studies of PAs in hospital settings published in 2013 and 2014 provided new positive evidence as to the contribution that PAs made to patient outcomes and resource use in a trauma-orthopaedic setting 32 and in low-and high-acuity emergency department (ED) settings. 33,34 One study 35 had reported that the indirect impact of employing PAs in a general surgical residency programme was to reduce the resident doctor workload, increase the doctors' ability to attend their training activities and improve results in their American Board of Surgery in Training Examination. In 2014, a study protocol was published for research investigating the substitution of medical doctors with PAs in hospitals in the Netherlands.…”
Section: Physician Associatesmentioning
confidence: 99%
“…There are many ways to determine provider efficiency in the literature . We chose number of new patients per resident per hour as one of the resident efficiency measurements for the following reasons: 1) it is a simple and easy way to measure; 2) residents tended to see relatively high‐acuity patients in the study ED, and therefore the patient acuity seemed to be less biased across different residents; 3) different shift lengths among residents, where PGY‐1 residents had 10‐hour shifts with the last 2 hours dedicated to “finishing up” and not picking up new patients and senior residents had 9‐hour shifts with the last hour dedicated to “finishing up” and not picking up new patients; and 4) crowding was measured hourly at the study ED, which matched well as the number of new patients per provider per hour, since such crowding statuses change dynamically and patient flow may be affected by different levels of crowding at the ED .…”
Section: Discussionmentioning
confidence: 99%
“…Such diverse provider efficiency reported in the literature raises the question of whether it is necessary to provide standard training on provider efficiency during EM residency training. Unfortunately, few studies in the current literature report on resident efficiency . Although previous studies addressed resident efficiency in general, there were neither efficiency comparisons among residents of different training levels nor dynamic comparisons during the entire academic year, which makes resident efficiency assessment less informative.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,11 Although the clinical value of residents compared to midlevel providers remains unknown in neurology, comparisons in emergency medicine and primary care suggest similar clinical value. [26][27][28] Our study explores some of the ways that departments and programs employ their new and existing faculty to assist with the loss of resident work, finding that faculties are frequently assisting residents in leading family meetings. This may have unintended consequences on the value of resident education.…”
Section: Discussionmentioning
confidence: 99%